Memorial de formação: começando uma nova história na educação infantil em Urucará - Santos, Leila Souza dos (Brasil, 2024)
This course completion work aims to present the context of my experience from childhood to adulthood and my studies from early childhood education to the completion of higher education. I highlighted several stages of my schooling during the period when I studied in rural areas and then the period when I studied in urban areas. The description of this memorial begins with personal and family stories, followed by information about the school career and professional trajectory, followed by stadium experiences. Writing this memoir was a great challenge, remembering some moments from my childhood moves me, however, it fills us with joy when we reflect that despite the challenges we faced, we managed to overcome them with great joy. Completing this memorial is part of the realization of my dream, which is to complete my degree in Pedagogy, and it is part of the results of everything I sowed throughout my days, what was sown since my childhood, going through all the stages of my life. my life, through all the schools I studied, and all the experiences I had. I finish this course conclusion work with a mind full of memories, some good, others not so much. And with this feeling of nostalgia, I remember the ups and downs, the anxieties and joys that often guided my steps. At this moment I am overcome by the feeling of happiness, because I finally managed to make my dream come true.